Biodegradable resin for spinning fiber production and preparation method thereof

By preparing a biodegradable resin for spinning fibers and using it as an additive for PLA spinning fibers, the problem of insufficient acid and alkali resistance of PLA spinning fibers is solved, and the corrosion resistance of the fibers is significantly improved.

CN119552340AInactive Publication Date: 2025-03-04JIANGSU ZHONGKE JINLONG CHEM
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510136672.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The lack of acid-base resistance of polylactic acid (PLA) spinned fibers limits its further application.

Method used

By preparing a biodegradable resin, including polypropylene carbonate diol, polyisocyanate, polyol crosslinking agent, catalyst and inorganic modified crosslinking agent, the polymer resin is formed by mechanical stirring and melt extrusion processes and used as additives for PLA spinning fibers.

Benefits of technology

The acid and alkali resistance of PLA spinned fibers is significantly improved, and the acid and alkali resistance of the fibers are prevented by forming a stable superhydrophobic film and a continuous physical barrier layer, thereby enhancing the corrosion resistance of the fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552340A_ABST
    Figure CN119552340A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of materials, and discloses biodegradable resin for spinning fiber production and a preparation method thereof.The biodegradable resin is prepared by taking polypropylene carbonate dihydric alcohol as a soft segment and polyisocyanate as a hard segment, adding a polyhydric alcohol cross-linking agent and an inorganic modified cross-linking agent and carrying out a melt extrusion process; the structure of the polyhydric alcohol cross-linking agent contains perfluoro chain segments and tert-butyl chain segments which are of an alternating structure, a stable super-hydrophobic membrane can be formed on the surface of the resin, permeation of acid and alkali is prevented, the inorganic modified cross-linking agent can participate in the polymerization process of the resin, a continuous physical barrier layer is formed in the resin, a corrosion medium is further prevented from permeating into the resin, and the corrosion resistance of the resin is improved. And the addition of the cross-linking agent enables the molecular chain of the resin to be more compact and the structure to be more compact, so that the resin shows excellent corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to a biodegradable resin for spinning fiber production and a preparation method thereof. Background Art

[0002] As an important part of the textile industry, spinning fiber has undergone a transformation from traditional natural fiber to modern synthetic fiber. In this process, polylactic acid (PLA) spinning fiber stands out in the textile field with its unique environmental protection characteristics and excellent physical properties. First of all, it has good biocompatibility and biodegradability. After being discarded, it can be completely decomposed into carbon dioxide and water in nature without causing pollution to the environment. Secondly, polylactic acid fiber has excellent physical and mechanical properties, such as high strength and high transparency, which enables it to meet the production needs of various textiles. In addition, polylactic acid fiber also has good UV resistance, low flammability and excellent processing performance, which further broadens its application range.

[0003] However, PLA spinning fiber is not resistant to acid and alkali, which has gradually become the main obstacle to the further application of limiters. Therefore, it needs to be modified. Studies have found that by adding functional auxiliary materials to PLA spinning fibers, the functionality of PLA spinning fibers can be improved. Among the many auxiliary additives, polypropylene carbonate, a carbon dioxide-based fully biodegradable resin, has good compatibility with polylactic acid, and thus becomes a reliable PLA spinning fiber additive. However, the acid and alkali resistance modification effect of adding polypropylene carbonate alone on PLA spinning fibers is still not obvious. Based on this, the present invention provides a biodegradable resin that can be used as an additive for PLA spinning fibers and can effectively enhance the acid and alkali resistance and other functionalities of PLA spinning fibers. Summary of the invention

[0004] In order to solve the problems mentioned in the background technology, the object of the present invention is to provide a biodegradable resin for spinning fiber production and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a biodegradable resin for spinning fiber production, the biodegradable resin comprises the following raw materials in parts by weight: 30-45 parts of polypropylene carbonate diol; 10-16 parts of polyisocyanate; 2-3.5 parts of polyol crosslinking agent; Catalyst 0.1-0.3 parts; 1-2 parts of inorganic modified crosslinking agent; The preparation method comprises the following steps: Step 1: Weigh and prepare all raw materials according to their weight; Step 2: Add polypropylene carbonate diol, polyisocyanate, polyol crosslinking agent, catalyst, and inorganic modified crosslinking agent into a mixer, control the temperature in the mixer to 80-90° C., and mechanically stir and mix at a stirring rate of 1000-2000 r / min for 4-6 hours to form a mixture; Step 3: feed the mixed material into a twin-screw extruder, control the temperature of sections 1-7 to 140-170°C, and the temperature of sections 8-15 to 160-180°C, extrude after 2-4 minutes, and then undergo a pelletizing process to obtain a biodegradable resin.

[0006] As a further embodiment of the present invention, the number average molecular weight of the polypropylene carbonate diol is 1500-4000; the polyisocyanate is any one of toluene diisocyanate, isophorone diisocyanate or hexamethylene diisocyanate.

[0007] In the above technical solution, polypropylene carbonate diol is used as the soft segment and polyisocyanate is used as the hard segment. Under the action of a catalyst, chain extension polymerization is carried out in the subsequent melt extrusion process to obtain a polyurethane type polymer resin, that is, a biodegradable resin.

[0008] As a further embodiment of the present invention, the specific preparation method of the polyol cross-linking agent is as follows: Toluene and 3-tert-butyl adipic acid are added to a polymerization kettle filled with nitrogen, and stirring is started until a uniform reaction liquid is formed. Then, 1,4-di(2',3'-epoxypropyl)perfluorobutane and a phase transfer catalyst are added to the reaction liquid. After the addition is completed, mechanical stirring is performed to make the mixture uniform. Heating is started, and the heating rate is controlled to be 2-3°C / min. The temperature is increased to 70-80°C. After stirring for 8-16 hours, the nitrogen is removed, the solvent is evaporated and removed, and the product is collected to obtain a polyol crosslinking agent.

[0009] As a further embodiment of the present invention, the molar ratio of 3-tert-butyl adipic acid to 1,4-di(2',3'-epoxypropyl)perfluorobutane is 1:0.8-1.

[0010] As a further embodiment of the present invention, the phase transfer catalyst is any one of tetramethylammonium bromide, tetrabutylammonium bromide or tetrabutylammonium hydrogen sulfate.

[0011] In the above technical scheme, a phase transfer catalyst is used to catalyze the continuous ring-opening esterification reaction between the active carboxyl substituents in the 3-tert-butyl adipic acid structure and the epoxy substituents at both ends of the 1,4-di(2',3'-epoxypropyl)perfluorobutane structure, thereby forming a macromolecular polymer with an alternating structure connected by ester bonds. Since a large number of substituted hydroxyl groups are generated during the ring-opening esterification reaction, these substituted hydroxyl groups can participate in the chain extension cross-linking reaction in the subsequent melt extrusion process, and thus can act as a cross-linking agent, i.e., a polyol cross-linking agent.

[0012] As a further embodiment of the present invention, the catalyst is any one of stannous octoate, dibutyltin diacetate or dibutyltin dilaurate.

[0013] As a further embodiment of the present invention, the specific preparation method of the inorganic modified crosslinking agent comprises the following steps: Step S1, dispersing illite in an ethanol aqueous solution with a volume fraction of 60-70%, then adding a silane coupling agent to the formed dispersion, after the addition, raising the temperature to 70-80°C, and heat-treating at this temperature for 6-9 hours, stopping heating, cooling and discharging, and obtaining modified illite; Step S2, mixing the modified illite with toluene, dispersing them into a uniform dispersion by ultrasonication, then adding glycidol, and then raising the temperature to 60-70° C., keeping the temperature for 4-8 hours, cooling and discharging the material to obtain an inorganic modified crosslinking agent.

[0014] As a further embodiment of the present invention, in step S1, the silane coupling agent is any one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane or N-aminoethyl-3-aminopropylmethyldimethoxysilane.

[0015] As a further solution of the present invention, in step S2, the mass ratio of glycidol to modified illite is 2-3:1.

[0016] In the above technical scheme, the surface of illite is firstly modified by using an aminosilane coupling agent to produce highly active amino substituents on its surface to obtain modified illite, which is then subjected to ring-opening addition reaction with the epoxy groups of glycidol. By controlling the excess of glycidol, one equivalent of amino substituents and two equivalents of epoxy groups can undergo ring-opening addition reaction, thereby producing a large number of active hydroxyl substituents on the surface of illite, which can also participate in the chain extension and cross-linking reaction in the subsequent melt extrusion process, i.e., an inorganic modified cross-linking agent.

[0017] A biodegradable resin for spinning fiber production is prepared by the preparation method.

[0018] Beneficial effects of the present invention: (1) The polyol crosslinking agent prepared by the present invention contains alternating perfluorinated segments and tert-butyl segments in its structure. These segments have extremely strong hydrophobicity. After they are introduced into the resin molecular chain through a crosslinking reaction, a stable super-hydrophobic film can be formed on the resin surface to prevent the penetration of acid and alkali. In addition, due to the polyol characteristics of the polyol crosslinking agent, the resin can be transformed from a linear structure to a three-dimensional network structure during the synthesis process, thereby improving the structural density of the resin and further preventing the penetration of corrosive media such as acid and alkali, so that the prepared resin has good corrosion resistance. After it is added as an additive to PLA spinning fiber, it can give the PLA spinning fiber excellent corrosion resistance.

[0019] (2) The present invention prepares an inorganic modified cross-linking agent and participates in the polymerization process of the resin. On the one hand, after the illite in the inorganic modified cross-linking agent enters the resin structure through a cross-linking reaction, the bonding between the illite and the resin can be greatly improved, so that the illite can overcome its own defect of easy agglomeration and be evenly dispersed in the resin. Then, using its own special lamellar structure, a continuous physical barrier layer is formed in the resin, which further prevents the corrosive medium from penetrating into the interior of the resin, thereby making the resin exhibit excellent corrosion resistance.

[0020] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0022] Figure 1 This is the infrared analysis test diagram of the polyol crosslinker. DETAILED DESCRIPTION

[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Preparation Example 1 The specific preparation method of the polyol cross-linking agent is as follows: Toluene and 0.3 g of 3-tert-butyl adipic acid were added to a polymerization kettle filled with nitrogen, and stirring was started until a uniform reaction liquid was formed. Subsequently, 0.4 g of 1,4-di(2',3'-epoxypropyl)perfluorobutane and tetrabutylammonium bromide were added to the reaction liquid. After the addition was completed, mechanical stirring was performed to uniformly stir the mixture. Heating was started, and the heating rate was controlled to be 2°C / min. The temperature was raised to 80°C. After stirring for 12 hours, the nitrogen was removed, the solvent was evaporated and removed, and the product was collected to obtain a polyol crosslinking agent.

[0025] The polyol crosslinking agent was made into potassium bromide tablets, and then infrared analysis was performed. The results are shown in Figure 1 , of which 3326cm -1 The characteristic absorption peak at 2880 cm -1 -2985cm -1 The characteristic absorption peaks appearing at 1746cm are the carbon-hydrogen characteristic absorption peaks of methyl and methylene. -1 The characteristic absorption peak at 1238 cm is the C=O characteristic absorption peak of the ester group. -1 The characteristic absorption peak that appears at is the CF characteristic absorption peak.

[0026] Preparation Example 2 The specific preparation method of the inorganic modified crosslinking agent comprises the following steps: Step S1, dispersing 1.8 g of illite in an ethanol aqueous solution with a volume fraction of 70%, and then adding 3.5 g of 3-aminopropyltriethoxysilane to the formed dispersion. After the addition, the temperature is raised to 75° C. and kept at this temperature for 8 hours, and the heating is stopped, and the temperature is lowered and the material is discharged to obtain modified illite; Step S2, 1.2 g of modified illite is mixed with toluene, and ultrasonically dispersed into a uniform dispersion, and then 3 g of glycidol is added, and then the temperature is increased to 65° C., and after keeping the temperature for 6 hours, the temperature is lowered and the material is discharged to obtain an inorganic modified crosslinking agent.

[0027] Example 1

[0028] A biodegradable resin for spinning fiber production, comprising the following raw materials in parts by weight: 30 parts of polypropylene carbonate diol; 10 parts of isophorone diisocyanate; 2 parts of polyol crosslinking agent; 0.1 part of dibutyltin dilaurate; 1 part of inorganic modified crosslinking agent; The preparation method of the biodegradable resin comprises the following steps: Step 1: Weigh and prepare all raw materials according to their weight; Step 2: adding polypropylene carbonate diol, isophorone diisocyanate, polyol crosslinking agent, dibutyltin dilaurate, and inorganic modified crosslinking agent into a mixer, controlling the temperature in the mixer to 80° C., and mechanically stirring and mixing at a stirring rate of 1000 r / min for 6 hours to form a mixture; Step 3: Feed the mixed material into a twin-screw extruder, control the temperature of sections 1-7 to 140°C, and the temperature of sections 8-15 to 160°C, extrude after 4 minutes, and then undergo a pelletizing process to obtain a biodegradable resin.

[0029] The number average molecular weight of the polypropylene carbonate diol is 4000; the preparation method of the polyol crosslinking agent is shown in Preparation Example 1; the preparation method of the inorganic modified crosslinking agent is shown in Preparation Example 2, and the same applies to the following.

[0030] Example 2

[0031] A biodegradable resin for spinning fiber production, comprising the following raw materials in parts by weight: 40 parts of polypropylene carbonate diol; 12 parts of toluene-2,4-diisocyanate; 3 parts of polyol crosslinking agent; 0.2 parts of dibutyltin dilaurate; 1.5 parts of inorganic modified crosslinking agent; The preparation method of the biodegradable resin comprises the following steps: Step 1: Weigh and prepare all raw materials according to their weight; Step 2: Add polypropylene carbonate diol, toluene-2,4-diisocyanate, polyol crosslinking agent, dibutyltin dilaurate, and inorganic modified crosslinking agent into a mixer, control the temperature in the mixer to 85° C., and mechanically stir and mix at a stirring rate of 1500 r / min for 5 hours to form a mixture; Step 3: Feed the mixed material into a twin-screw extruder, control the temperature of sections 1-7 to 160°C, and the temperature of sections 8-15 to 170°C, extrude after 3 minutes, and then undergo a pelletizing process to obtain a biodegradable resin.

[0032] Example 3

[0033] A biodegradable resin for spinning fiber production, comprising the following raw materials in parts by weight: 45 parts of polypropylene carbonate diol; 16 parts of toluene-2,4-diisocyanate; 3.5 parts of polyol crosslinking agent; 0.3 parts of dibutyltin diacetate; 2 parts of inorganic modified crosslinking agent; The preparation method of the biodegradable resin comprises the following steps: Step 1: Weigh and prepare all raw materials according to their weight; Step 2: Add polypropylene carbonate diol, toluene-2,4-diisocyanate, polyol crosslinker, dibutyltin diacetate, and inorganic modified crosslinker into a mixer, control the temperature in the mixer to 90° C., and mechanically stir and mix at a stirring rate of 2000 r / min for 4 hours to form a mixture; Step 3: Feed the mixed material into a twin-screw extruder, control the temperature of sections 1-7 to 170°C, and the temperature of sections 8-15 to 180°C, extrude after 2 minutes, and then undergo a pelletizing process to obtain a biodegradable resin.

[0034] Comparative Example 1 A biodegradable resin for spinning fiber production, comprising the following raw materials in parts by weight: 40 parts of polypropylene carbonate diol; 12 parts of toluene-2,4-diisocyanate; 0.2 parts of dibutyltin dilaurate; 1.5 parts of inorganic modified crosslinking agent; The preparation method of the biodegradable resin comprises the following steps: Step 1: Weigh and prepare all raw materials according to their weight; Step 2: Add polypropylene carbonate diol, toluene-2,4-diisocyanate, dibutyltin dilaurate, and an inorganic modified crosslinking agent into a mixer, control the temperature in the mixer to 85° C., and mechanically stir and mix at a stirring rate of 1500 r / min for 5 hours to form a mixture; Step 3: Feed the mixed material into a twin-screw extruder, control the temperature of sections 1-7 to 160°C, and the temperature of sections 8-15 to 170°C, extrude after 3 minutes, and then undergo a pelletizing process to obtain a biodegradable resin.

[0035] Comparative Example 2 A biodegradable resin for spinning fiber production, comprising the following raw materials in parts by weight: 40 parts of polypropylene carbonate diol; 12 parts of toluene-2,4-diisocyanate; 3 parts of polyol crosslinking agent; 0.2 parts of dibutyltin dilaurate; Illite 1.5 parts; The preparation method of the biodegradable resin comprises the following steps: Step 1: Weigh and prepare all raw materials according to their weight; Step 2: Add polypropylene carbonate diol, toluene-2,4-diisocyanate, polyol crosslinking agent, dibutyltin dilaurate, and illite into a mixer, control the temperature in the mixer to 85° C., and mechanically stir and mix at a stirring rate of 1500 r / min for 5 hours to form a mixture; Step 3: Feed the mixed material into a twin-screw extruder, control the temperature of sections 1-7 to 160°C, and the temperature of sections 8-15 to 170°C, extrude after 3 minutes, and then undergo a pelletizing process to obtain a biodegradable resin.

[0036] Comparative Example 3 A biodegradable resin for spinning fiber production, comprising the following raw materials in parts by weight: 40 parts of polypropylene carbonate diol; 12 parts of toluene-2,4-diisocyanate; 3 parts of polyol crosslinking agent; 0.2 parts of dibutyltin dilaurate; The preparation method of the biodegradable resin comprises the following steps: Step 1: Weigh and prepare all raw materials according to their weight; Step 2: Add polypropylene carbonate diol, toluene-2,4-diisocyanate, polyol crosslinking agent, and dibutyltin dilaurate into a mixer, control the temperature in the mixer to 85° C., and mechanically stir and mix at a stirring rate of 1500 r / min for 5 hours to form a mixture; Step 3: Feed the mixed material into a twin-screw extruder, control the temperature of sections 1-7 to 160°C, and the temperature of sections 8-15 to 170°C, extrude after 3 minutes, and then undergo a pelletizing process to obtain a biodegradable resin.

[0037] Test Case a. Referring to the standard GB / T 19277-2003, the biodegradable resins in the examples and comparative examples were subjected to biodegradation tests, and the test results are recorded in Table 1: Table 1 - Biodegradation test results

[0038] b. According to a mass ratio of 10:1, polylactic acid was melt-spun with the biodegradable resin prepared in the embodiment of the present invention and the comparative example, and the polylactic acid was used as the warp and weft yarns to form a fabric by a large circular machine. The fabric was cut into 20 cm × 20 cm samples, and the fabric was immersed in an acidic solution with a pH of 3 and an alkaline solution with a pH of 10, respectively. After 24 hours, the fabric was taken out and the surface of the fabric sample was observed to see if there was any corrosion. The test results are recorded in Table 2: Table 2-Corrosion resistance test results

[0039] Based on the above test results, it can be seen that the biodegradable resin prepared by the present invention has good biodegradability, and the fabric made by mixing it with polylactic acid as an additive and melt spinning has good corrosion resistance.

[0040] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.

[0041] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a biodegradable resin for spinning fiber production, characterized in that: The biodegradable resin comprises the following raw materials in parts by weight: 30-45 parts of polypropylene carbonate diol; 10-16 parts of polyisocyanate; 2-3.5 parts of polyol crosslinking agent; Catalyst 0.1-0.3 parts; 1-2 parts of inorganic modified crosslinking agent; The preparation method comprises the following steps: Step 1: Weigh and prepare all raw materials according to their weight; Step 2: Add polypropylene carbonate diol, polyisocyanate, polyol crosslinking agent, catalyst, and inorganic modified crosslinking agent into a mixer, control the temperature in the mixer to 80-90° C., and mechanically stir and mix at a stirring rate of 1000-2000 r / min for 4-6 hours to form a mixture; Step 3: Feed the mixed material into a twin-screw extruder, control the temperature of sections 1-7 to 140-170°C, and the temperature of sections 8-15 to 160-180°C, extrude after 2-4 minutes, and then pelletize to obtain a biodegradable resin; The specific preparation method of the polyol cross-linking agent is as follows: Toluene and 3-tert-butyl adipic acid are added to a polymerization kettle filled with nitrogen, stirring is started until a uniform reaction liquid is formed, and then 1,4-di(2',3'-epoxypropyl)perfluorobutane and a phase transfer catalyst are added to the reaction liquid. After the addition is completed, mechanical stirring is performed to make the reaction liquid uniform. Heating is started, and the heating rate is controlled to be 2-3°C / min. The temperature is raised to 70-80°C. After stirring for 8-16 hours at the same temperature, the nitrogen is removed, the solvent is evaporated and removed, and the product is collected to obtain a polyol crosslinking agent. The specific preparation method of the inorganic modified crosslinking agent comprises the following steps: Step S1, using a silane coupling agent to perform surface functionalization modification on illite to obtain modified illite; Step S2: In a toluene medium, the modified illite is treated with glycidol to obtain an inorganic modified crosslinking agent.

2. The method for preparing a biodegradable resin for spinning fiber production according to claim 1, characterized in that: The number average molecular weight of the polypropylene carbonate diol is 1500-4000; the polyisocyanate is any one of toluene diisocyanate, isophorone diisocyanate or hexamethylene diisocyanate.

3. The method for preparing a biodegradable resin for spinning fiber production according to claim 1, characterized in that: The molar ratio of the 3-tert-butyl adipic acid to 1,4-di(2',3'-epoxypropyl)perfluorobutane is 1:0.8-1.

4. The method for preparing a biodegradable resin for spinning fiber production according to claim 1, characterized in that: The phase transfer catalyst is any one of tetramethylammonium bromide, tetrabutylammonium bromide or tetrabutylammonium hydrogen sulfate.

5. The method for preparing a biodegradable resin for spinning fiber production according to claim 1, characterized in that: The catalyst is any one of stannous octoate, dibutyltin diacetate or dibutyltin dilaurate.

6. The method for preparing a biodegradable resin for spinning fiber production according to claim 1, characterized in that: In step S1, the silane coupling agent is any one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane or N-aminoethyl-3-aminopropylmethyldimethoxysilane.

7. The method for preparing a biodegradable resin for spinning fiber production according to claim 1, characterized in that: In step S2, the mass ratio of glycidol to modified illite is 2-3:

1.

8. A biodegradable resin for spinning fiber production, characterized in that: The method is prepared according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Polypropylene carbonate particles as well as preparation method and application thereof

    CN116162222A

  • Anti-yellowing polyurethane adhesive and application thereof

    CN118308060A

  • Polyurethane insulating resin as well as preparation method and application thereof

    CN119192825A

  • Electronic device for guaranteeing write atomicity based on non-volatile memory and operation method thereof

    KR1020230109022A